Singularity Calculation and Kinematics Modeling of High Speed Six-bar Parallel Measuring Machine - Zhao Lei; Zhao Xinhua; Wang Shoujun; Ge Weimin; Wang Xiaofei (Jixie chuandong)
The parallel robots have some advantages of strong load capacity,fast speed moving and large stiffness,it makes up for the deficiency of series robot and will become a potential motion platform with high speed and high precision. The kinematics model and closed chain constraint equations are established based on the constrain relationship between the primary and passive joints in three chains for solving these problems of poor dynamics performances and uncontrolled motion about the designed six- bar parallel measuring machine.The calculation of space singularity of measuring machine is realized through the calculation of 15 generations by using normalized genetic algorithm through converting the singularity solution into calculation of LMI extreme-value,the normalized genetic algorithm calculation accuracy reaches 1. 689 × 10- 5. The proposed method avoids of mass computation compared to the traditional way based on the analysis of Jacobin matrix and has obvious advantages of high accuracy and fast convergence rate. The theory foundation is established for realizing measuring work in high speed and high accuracy.